Better Attitudes toward Foreigners: Effects of Dual-Identity, Identity Fusion with the Country and Humanity - Landabur Ayala, Rodrigo; Wilson Alcalde, Juan E. (Psykhe, 2022)
Social categorization implies a difference between “we” and “they”, motivating people to create or maintain a positive group distinctiveness, which leads to intergroup bias. The common ingroup identity model proposes that recategorization from separated subgroups into an inclusive superordinate group can reduce intergroup bias. However, further research shows that bias reduction is more likely when a dual identity is created, wherein the ingroup and superordinate identities are simultaneously salient and, thus, ingroup distinctiveness is safeguarded within this recategorization process. The present study examined the effect of dual versus common identity representations on attitudes toward foreigners, as well as the dependence of this effect on identity fusion with the country and all humanity. Participants (n = 149) were assigned to one of two conditions: Worldwide (common) Identity, and Dual-Identity. Regression analysis indicated that, relative to the worldwide identity condition, the dual-identity condition produced more positive attitudes toward foreigners: less willingness to fight, greater perceived common identity, and stronger trust. This last result was moderated by identity fusion with the country and all humanity. Findings suggest that to reduce intergroup bias, it is important that people perceive themselves as members of all humanity without having to relinquish their ingroup identity.